Dinamika Islam Politik di Indonesia pada Era Reformasi (1998-2001) - Bustamam-Ahmad, Kamaruzzaman (Al-Jamiah Research Centre, 2003)
This article discusses the political attitude of some Indonesian Muslims to the reformation era of Indonesia. Euphorically, they responded the reformation in the same way as in the early history of Indonesian politics, i.e., they are interested much in struggling their political interest in the formalistic ways. This study has found that the Islamic figures who struggling political Islam in the substantive ways are entrapped in formalistic struggle. Compared to the era of Old and New Order political system, some politician Muslims hardly offer new political strategies. Their political attitudes have been promoted so far are merely on the following three points. First is an interest to raise their political parties to the power. Second is to pose their groups without any good quality agenda. Third, inconsistency of some figure in struggling for Muslim society, they struggling for their own group. Instead, It seem that the attitude of some elite politician Muslims is influenced by political changes and their religious understandings. It is clear that if political Islam is struggled without any good and distinct concept or agenda, the politician Muslims would face some obstacles which are difficult to be solved. Therefore, basic wide-ranging understanding is necessary for politician Muslims in comprehending some political affairs in Indonesia.